Transcatheter Interatrial Shunt Device for the Treatment of Heart Failure With Preserved Ejection Fraction (REDUCE LAP-HF I [Reduce Elevated Left Atrial Pressure in Patients With Heart Failure]): A Phase 2, Randomized, Sham-Controlled Trial. Issue 4 (23rd January 2018) - Feldman, Ted; Mauri, Laura; Kahwash, Rami; Litwin, Sheldon; Ricciardi, Mark J.; van der Harst, Pim; Penicka, Martin; Fail, Peter S.; Kaye, David M.; Petrie, Mark C.; Basuray, Anupam; Hummel, Scott L.; et al.
Abstract : Background: In nonrandomized, open-label studies, a transcatheter interatrial shunt device (IASD, Corvia Medical) was associated with lower pulmonary capillary wedge pressure (PCWP), fewer symptoms, and greater quality of life and exercise capacity in patients with heart failure (HF) and midrange or preserved ejection fraction (EF ≥40%). We conducted the first randomized sham-controlled trial to evaluate the IASD in HF with EF ≥40%. Methods: REDUCE LAP-HF I (Reduce Elevated Left Atrial Pressure in Patients With Heart Failure) was a phase 2, randomized, parallel-group, blinded multicenter trial in patients with New York Heart Association class III or ambulatory class IV HF, EF ≥40%, exercise PCWP ≥25 mm Hg, and PCWP-right atrial pressure gradient ≥5 mm Hg. Participants were randomized (1:1) to the IASD versus a sham procedure (femoral venous access with intracardiac echocardiography but no IASD placement). The participants and investigators assessing the participants during follow-up were blinded to treatment assignment. The primary effectiveness end point was exercise PCWP at 1 month. The primary safety end point was major adverse cardiac, cerebrovascular, and renal events at 1 month. PCWP during exercise was compared between treatment groups using a mixed-effects repeated measures model analysis of covariance that included data from all available stages of exercise. Results: A total of 94 patients were enrolled, of whom 44 met inclusion/exclusion criteria and were randomized to the IASD (n=22) and control (n=22) groups. Mean age was 70±9 years, and 50% were female. At 1 month, the IASD resulted in a greater reduction in PCWP compared with sham control ( P =0.028 accounting for all stages of exercise). Peak PCWP decreased by 3.5±6.4 mm Hg in the treatment group versus 0.5±5.0 mm Hg in the control group ( P =0.14). There were no peri-procedural or 1-month major adverse cardiac, cerebrovascular, and renal events in the IASD group and 1 event (worsening renal function) in the control group ( P =1.0). Conclusions: In patients with HF and EF ≥40%, IASD treatment reduces PCWP during exercise. Whether this mechanistic effect will translate into sustained improvements in symptoms and outcomes requires further evaluation. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT02600234. Abstract : Supplemental Digital Content is available in the text.